Possible Change in Distribution Areas of Abies in Kastamonu due to Global Climate Change - Erturk, Nihat; Aricak, Burak; Sevik, Hakan; Yigit, Nurcan (Kastamonu Univ, 2024)
Aim of the study: In the process of global climate change (GCC), the migration mechanism needed especially for forest trees must be provided by humans. For this purpose, contrary to the previous studies, detailed studies to be carried out on small areas are needed. Area of study: In the present study carried out in Kastamonu Regional Directorate of Forestry, which performs the highest level of wood production in Turkiye, it was aimed to specify the actual distribution areas of the Abies and the change in their suitable distribution areas due to GCC. Material and methods: In this study, besides the existing distribution areas and the potential future distribution areas, also the suitable distribution areas were determined by using SSP 126, SSP 370, and SSP 585 scenarios for the years 2040, 2070, and 2100 for Abies at Kastamonu. Main results: The results achieved there showed that, depending on the results of climate change, distribution areas of Abies populations would change in the future and this change would be in form of an increase in general. Research highlights: This species (Abies) seems incapable of keeping up with such changes without human intervention. Thus, considering the study results, it is recommended to make necessary amendments to the forest management plans.
Keywords: management plans. Global Climate Change; Abies nordmanniana; Abies; SSPs Scenarios